2020
DOI: 10.1007/s10554-020-01980-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute pulmonary embolism multimodality imaging prior to endovascular therapy

Abstract: The manuscript discusses the application of CT pulmonary angiography, ventilation-perfusion scan, and magnetic resonance angiography to detect acute pulmonary embolism and to plan endovascular therapy. CT pulmonary angiography offers high accuracy, speed of acquisition, and widespread availability when applied to acute pulmonary embolism detection. This imaging modality also aids the planning of endovascular therapy by visualizing the number and distribution of emboli, determining ideal intra-procedural cathet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 146 publications
(205 reference statements)
0
11
0
2
Order By: Relevance
“…With technological advances in recent years, CTPA can directly show the thrombus in the pulmonary artery bed up to the segmental level (23). Although acute PE cannot be observed with the help of CTPA, which we prefer for definite and rapid diagnosis of PE in ED, it can show alternative diagnoses for the patient's clinical picture (24). In a study evaluating the detection of acute PE, when CTPA was compared with pulmonary angiography, which is the gold standard, it was observed that CTPA had 91% accuracy (25).…”
Section: Discussionmentioning
confidence: 99%
“…With technological advances in recent years, CTPA can directly show the thrombus in the pulmonary artery bed up to the segmental level (23). Although acute PE cannot be observed with the help of CTPA, which we prefer for definite and rapid diagnosis of PE in ED, it can show alternative diagnoses for the patient's clinical picture (24). In a study evaluating the detection of acute PE, when CTPA was compared with pulmonary angiography, which is the gold standard, it was observed that CTPA had 91% accuracy (25).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the importance of imaging in establishing prompt and accurate diagnosis and in guiding the proper treatment of many life-threatening emergency conditions including cardiovascular, abdominal [15] and gastrointestinal, neurological, musculoskeletal, obstetrical, genitourinary [16] and pulmonary conditions [17] in all age groups, as well as in trauma [18,19]. Imaging is an integral and crucial part in stroke diagnosis and image-guided endovascular treatment, and AI has a role to determine the presence and extent of involvement of brain parenchyma [20,21].…”
Section: Noncommunicable Diseasesmentioning
confidence: 99%
“…Nowadays, the diagnosis of PE is mainly based on radiomics, which has also been evaluated for the diagnosis of PI [ 18 , 19 ]. In particular, CT pulmonary angiography (CTPA) is the gold standard with high accuracy [ 20 ] and dual-energy CTPA allows the identification of perfusion defects [ 20 , 21 ]. Acute PE could cause partial or complete obstruction of pulmonary vasculature but the latter can lead to PI, which appears on CTPA as ground-glass opacity with reticular changes or wedge-shaped consolidation with its base toward the pleural surface (Hampton hump) and truncated apex toward the hilum, without air bronchogram [ 7 , 20 , 22 , 23 ].…”
Section: Possible Diagnostic Criteriamentioning
confidence: 99%
“…Moreover, diffused or localized pleural effusion and thickened vessels are other salient findings of PI at CTPA examination [ 23 ]. Moreover, complete occlusions appear tortuous and calcified [ 20 ]. It is important to consider the presence of artifacts due to breathing, which could lead to misdiagnosis [ 22 , 24 ] ( Figure 1 ).…”
Section: Possible Diagnostic Criteriamentioning
confidence: 99%